The Glocalization of Sport: A Research Field for Social Innovation - Zijing Li; Arnaud Waquet; Philippe Campillo (Social Sciences)
This article explores the emergence of the concept of glocalization in contemporary societies and more precisely, the glocalization of sport to highlight a social innovation borne through the interaction between global dynamics and local specificities in the development of sport. The glocalization, considered as a theorical framework to rethink local social innovation which answered to the limit of the globalization, is examined in this article through an in-depth bibliographic analysis conducted using the Lillocat metasearch engine (covering 354 articles since 1992 across 11 thematic areas, 29 of which are related to sports). The use of IRaMuTeQ software version 0.7 alpha2 (Interface for Multidimensional Text and Questionnaire Analysis) enabled comprehensive textual and lexical analyses, including frequency analyses, hierarchical classifications, and principal component analyses (PCA). These analyses were presented in the form of figures such as histograms, dendrograms, and word clouds, thereby facilitating the identification of lexical co-occurrence relationships and the understanding of emerging trends. Findings reveal that glocalization enables sports organizations to integrate global strategies with local cultural identities, fostering fan engagement, economic sustainability, and cultural diversity. Global events such as the FIFA World Cup, the NBA’s international expansion, and the Tour de France illustrate how global frameworks adapt to local contexts. Glocalization emerges as a strategic driver of social innovation, balancing internationalization with localized adaptation. This study provides insights for researchers and practitioners, considering glocalization as a theorical framework useful for the analysis of a local social innovation in the context of globalization and sport as a propitious field of research.